2019
DOI: 10.1093/europace/euz159
|View full text |Cite
|
Sign up to set email alerts
|

Extent and spatial distribution of left atrial arrhythmogenic sites, late gadolinium enhancement at magnetic resonance imaging, and low-voltage areas in patients with persistent atrial fibrillation: comparison of imaging vs. electrical parameters of fibrosis and arrhythmogenesis

Abstract: Aims Atrial fibrosis contributes to arrhythmogenesis in atrial fibrillation and can be detected by MRI or electrophysiological mapping. The current study compares the spatial correlation between delayed enhancement (DE) areas to low-voltage areas (LVAs) and to arrhythmogenic areas with spatio-temporal dispersion (ST-Disp) or continuous activity (CA) in atrial fibrillation (AF). Methods and results Sixteen patients with persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 25 publications
2
46
0
Order By: Relevance
“…[ 63 ] Chen et al studied the correlation between delayed enhancement on CMR imaging and LVAs on electroanatomic mapping in 16 patients with persistent AF. [ 64 ] There was a mismatch between delayed enhancement areas and LVAs; delayed enhancement was present in 61% of LVAs, whereas low voltage was present in 28% of delayed enhancement areas. In another recent multimodal examination of AF substrate, Zghaib et al demonstrated that LGE-MRI, high-density mapping and point-by-point mapping with the ablation catheter demonstrated good correlation in delineating electroanatomical AF substrate, providing some enthusiasm for the routine use of CMR imaging.…”
Section: How Best To Define Abnormal Atrial Substrate: Pitfallsmentioning
confidence: 99%
“…[ 63 ] Chen et al studied the correlation between delayed enhancement on CMR imaging and LVAs on electroanatomic mapping in 16 patients with persistent AF. [ 64 ] There was a mismatch between delayed enhancement areas and LVAs; delayed enhancement was present in 61% of LVAs, whereas low voltage was present in 28% of delayed enhancement areas. In another recent multimodal examination of AF substrate, Zghaib et al demonstrated that LGE-MRI, high-density mapping and point-by-point mapping with the ablation catheter demonstrated good correlation in delineating electroanatomical AF substrate, providing some enthusiasm for the routine use of CMR imaging.…”
Section: How Best To Define Abnormal Atrial Substrate: Pitfallsmentioning
confidence: 99%
“…LVAs are found mainly on the LA septum, anterior LA, and posterior LA 16 . Chen et al 17 reported that LGE sites were present in 61% of LVAs, whereas LVAs were present at 28% of LGE sites. These findings indicated that the distribution of the LGE sites could not completely overlap with that of the LVAs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the main limitation of this imaging modality for fibrosis assessment is the suboptimal reproducibility of the results, mainly due to variable acquisition protocols and processing techniques that increase inter‐observer variability 35 . There are still discrepancies in the extent and distribution of late‐gadolinium enhancement‐MRI areas and EAM‐identified LVZs in patients with AF 36 …”
Section: Discussionmentioning
confidence: 99%